THE EFFECT OF THE RUPIAH EXCHANGE RATE AND INFLATION ON STOCK PRICES - Hijayanti, Siti Nurul; Manda, Gusganda Suria (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to examine how the rupiah exchange rate affects the company's stock price. In the research we conducted, the data analysis method we used was multiple linear regression analysis. The research was conducted in the period 2021-2023, with the research population being all Property & Real Estate sector companies listed on the Indonesia Stock Exchange (IDX). The sample acquisition technique in this study was random sampling, so there were 10 companies in the Property & Real Estate sector that we made as samples in this study. The results showed that the rupiah exchange rate has an influence on stock prices, while inflation has no effect on stock prices. Simultaneously the rupiah exchange rate and inflation have an influence on stock prices.